2015
DOI: 10.1182/blood-2014-11-612770
|View full text |Cite
|
Sign up to set email alerts
|

Astatine-211 conjugated to an anti-CD20 monoclonal antibody eradicates disseminated B-cell lymphoma in a mouse model

Abstract: α-Emitting radionuclides deposit a large amount of energy within a few cell diameters and may be particularly effective for radioimmunotherapy targeting minimal residual disease (MRD). To evaluate this hypothesis, (211)At-labeled 1F5 monoclonal antibody (mAb) (anti-CD20) was studied in both bulky lymphoma tumor xenograft and MRD animal models. Superior treatment responses to (211)At-labeled 1F5 mAb were evident in the MRD setting. Lymphoma xenograft tumor-bearing animals treated with doses of up to 48 µCi of (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…The trend for a decreasing ratio of CD20 + cells compared with CD3 + cells occurs as T cells complete their long developmental process in the thymus and begin to migrate into the periphery beginning around week 14 post-engraftment. For testing ACI-mediated strategies against B cell epitopes, it is possible to inject bioluminescent tumor lines expressing these epitopes into these mice to assay for functionality of infused CAR T cells 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…The trend for a decreasing ratio of CD20 + cells compared with CD3 + cells occurs as T cells complete their long developmental process in the thymus and begin to migrate into the periphery beginning around week 14 post-engraftment. For testing ACI-mediated strategies against B cell epitopes, it is possible to inject bioluminescent tumor lines expressing these epitopes into these mice to assay for functionality of infused CAR T cells 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that parallel bispecific antibodies targeting CD38 on myeloma cells or CD45 on AML cells work as well as the CD20 antibodies published in Cancer Research(15) (and unpublished data, Green and Press). We are currently scaling up production of the bispecific antibodies for human clinical trials.…”
Section: Introductionmentioning
confidence: 80%
“…These beta-particle emitting radionuclides are readily available, have favorable emission characteristics, and are stably retained on antibodies using simple radiolabeling methods(10). Recently, the increased availability of α–emitter radionuclides, in conjunction with advances in radiochemistry leading to radiolabeling platforms capable of providing critical stability to α–particle-labeled biomolecules,(12) has led to promising results using α–emitter RIT in leukemia(13,14), lymphoma (15) and MM (Green and Press unpublished observations). Based on their physical characteristics, α-emitters may be particularly efficacious in minimal residual disease (MRD) settings, where isolated cells and small tumor clusters prevail.…”
Section: Introductionmentioning
confidence: 99%
“…First successful cancer treatment experiments in an animal model with astatine‐boron‐cage‐labelled antibodies were reported by Green et al…”
Section: Investigations Of Astatinated Organic Compoundsmentioning
confidence: 99%